Options for waterpipe product regulation: A systematic review on product characteristics that affect attractiveness, addictiveness and toxicity of waterpipe use - Kienhuis, Anne S. (Tob Induc Dis, 2020)
INTRODUCTION: Despite its known adverse effects on human health, waterpipe smoking is increasing in popularity worldwide. However, compared to cigarettes, regulation of waterpipe product smoking lags behind and presents unique challenges. In search for regulatory options, this systematic review analyzes 36 studies on the differential effects on human health of the waterpipe characteristics including smoking products, heating sources, device components, and packages. METHODS: A systematic review was performed according to PRISMA guidelines, revealing 443 unique citations. After screening, 36 studies were included in the results. Research articles were selected to inform on differential effects caused by product characteristics on adverse health effects, attractiveness, addictiveness and prevalence of waterpipe use. RESULTS: Flavors are the key aspect that defines attractiveness of waterpipe product smoking. All waterpipe products, with or without nicotine, produce toxicants in similar quantities as cigarettes. Heating sources for waterpipe tobacco include charcoals and electrical heating. Both heating sources increase toxicant emissions in different ways. Hoses and mouth tips are device components that are often shared in waterpipe smoking. Sharing influences attractiveness by enriching the social experience. At the same time, it influences the transfer of infectious diseases by bacteria and viruses from one smoker to another. Studies showed that more generic and less attractive packages with health warnings are effective in reducing the attractiveness of waterpipe smoking. CONCLUSIONS: Based on our findings, we advise to include all waterpipe products, tobacco and non-tobacco, with or without nicotine, in tobacco product regulations and smoking bans in order to: ban waterpipe molasses with characterizing flavors or ban the use of flavorings at any level; mandate dissemination of information on all waterpipe tobacco elements to the national regulator; prescribe testing to regulate contents of waterpipe smoking products and heating sources. Moreover, we advise to stimulate research on emissions of waterpipes.